Long Non‐Coding RNA , Like NEAT1 and MALAT1 , in Asthma: Mechanisms and Therapeutic Potential - Ashlyn Poole; Ingrid Laing; Ryan Mead‐Hunter; Peter Le Souef; Guicheng Zhang (Clinical & Experimental Allergy, 2026)
ABSTRACT Asthma affects millions worldwide. Long non‐coding RNA (lncRNA) are emerging as important factors in the pathophysiology of asthma and respiratory illnesses. LncRNA serve important regulatory roles in numerous pathways, especially gene expression. Nuclear paraspeckle assembly transcript 1 (NEAT1) and metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) are two of the most well‐studied lncRNA. This review highlights the current evidence of mechanisms involving lncRNA, particularly NEAT1 and MALAT1, in asthma pathophysiology and viral‐induced exacerbations, and as novel targets for therapies targeting asthma, asthma‐related symptoms and airway remodelling.